Experimental and numerical simulation studies on the mechanical properties and failure characteristics of rock masses with weak interlayers. - Feng Wang; Yong Yang; Yuchi Wang; Zhaoyu Li; Baoliang Han; Yang Bin; Jun Hu; Yujiang Yang; Zhiguo Xia (PLoS ONE)
To elucidate the mechanical properties and failure behaviors of rock-like materials with weak interlayers of varying inclinations and thicknesses, uniaxial compression tests were conducted on such rock-like materials. The effects of interlayer inclination and thickness on the acoustic emission ringing counts and macroscopic fracture of the rock-like materials were investigated. From a mesoscopic perspective, the crack initiation and propagation processes, stress field distribution characteristics, and energy evolution laws of the rock-like materials with weak interlayers were analyzed. Additionally, the failure modes obtained from the experiments were compared with those from numerical simulations. The results indicate that as the interlayer thickness or inclination increases, the peak strength and elastic modulus of the specimens gradually decrease. Specifically, under the influence of interlayer thickness, the peak strength and elastic modulus decrease by 38.27% and 68.69%, respectively, while under the influence of interlayer inclination, they decrease by 51.28% and 8.47%, respectively. The energy dissipation of the specimens is mainly concentrated in the post-peak stage and is closely related to the propagation and coalescence of microcracks within the rock mass. The initial failure typically occurs at the weak interlayer or at the interface between layers. The weak interlayer serves as the primary zone for microcrack initiation, and the stress concentration zones are mainly distributed on the upper and lower sides of the interlayer. The failure mode transitions gradually from tensile failure to shear failure, ultimately dominated by a combined tensile-shear failure. Moreover, the failure primarily manifests as the overall failure of the specimens with weak interlayers.